8-4+2R-4R+8R=

Simple and best practice solution for 8-4+2R-4R+8R= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-4+2R-4R+8R= equation:


Simplifying
8 + -4 + 2R + -4R + 8R = 0

Combine like terms: 8 + -4 = 4
4 + 2R + -4R + 8R = 0

Combine like terms: 2R + -4R = -2R
4 + -2R + 8R = 0

Combine like terms: -2R + 8R = 6R
4 + 6R = 0

Solving
4 + 6R = 0

Solving for variable 'R'.

Move all terms containing R to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 6R = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 6R = 0 + -4
6R = 0 + -4

Combine like terms: 0 + -4 = -4
6R = -4

Divide each side by '6'.
R = -0.6666666667

Simplifying
R = -0.6666666667

See similar equations:

| 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 | | -(12+2r)-(r+8)=-7r+3r | | 10U-2U= | | 6x^2-13x+4= | | 4.29b-0.692=11.749 | | 3[2(5x-7)-3(4x-6)]-4[5(x-1)-7x]=6[-4(x+2)+7x] | | 6+5(8w-9)= | | 36=2L+W | | 1w+5=4 | | 3-2(x-4)=2x-5 | | 3(4x+1)=3+12x-2 | | (X+10)+(4x-20)=90 | | 7R*2+8R+8R= | | 3x(.29)=3 | | 1y+-4x= | | 8v-18=26+3v | | 18+4(-4)= | | 50-40x=200 | | 3t-t=20 | | X^5-2x^4+x^3-x^2+2x-1=0 | | 50+40x=200 | | 5a-2b=8displayngb |

Equations solver categories